Effectiveness of automatic cam programming using machining templates for the manufacture of special production tooling - Kowalski, Maciej (Strojniški vestnik, 2021)
The paper presents the methodology and implementation of original Automatic CAM programming using machining templates (ACPUT) dedicated to manufacturing special technological tooling. The development of ACPUT was inspired by the observation that although modern computer-aided design (CAD) / computer-aided manufacturing (CAM) systems can automatically create CAM programs, their universality makes them both difficult to use and inefficient because the programs created this way often contain errors. The presented programming procedure includes the development of specific machining templates based on technological knowledge gathered in a specially prepared database. These templates are dedicated to a group of parts characterized by the similarity of their geometric features. ACPUT makes it possible to reduce(in comparison to traditional CAM programming) the time required to develop a machining program, thereby positively impacting the total cost of tooling production. The paper aims to present results of testing the effectiveness of the use of ACPUT by technicians with different levels of experience (expert and beginner). The tests were carried out on special tooling - assembly equipment for plastic pipes, and compared program preparation time, machining time, and production costs.
Keywords: avtomatizacija tehnološke priprave; CNC programiranje; CNC programming; generative CAM process; generativni proces CAM; knowledge-based engineering; na znanju temelječi inženiring; technology design automation